1993
DOI: 10.1002/aic.690390404
|View full text |Cite
|
Sign up to set email alerts
|

Settling behaviors of iron oxide suspensions

Abstract: This article shows the settling behaviors of flocculated, magnetic and nonmagnetic iron oxide suspensions. It is unique, since in the literature on settling of model submicron flocculated particulate suspensions there is no direct visualization of the structures and how they change during settling. Channeling, cracking, and a novel collapse phenomenon were detected during settling. Causes were investigated using lapse videorecording for side and top views. The effect of air bubbles was shown to contribute to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 25 publications
4
32
0
Order By: Relevance
“…For the 2:l diluted sample, the solids settled 3.8 cm (62% of the 6.13 cm total height) in about 24 hours. This behavior is consistent with that commonly observed in the sedimentation of certain metal hydroxides (see, for example Glasrud et al 1993) and has been observed with both Hanford wastes and waste simulants (Rector and Bunker 1995). supernatant liquid or an equimolar sodium hydroxide and salt solution), differences in waste chemistry make applying these results to the current mobilization and retrieval scenario rather difficult.…”
Section: Settled Slurry Volume Fraction and Sedimentation Behaviorsupporting
confidence: 88%
“…For the 2:l diluted sample, the solids settled 3.8 cm (62% of the 6.13 cm total height) in about 24 hours. This behavior is consistent with that commonly observed in the sedimentation of certain metal hydroxides (see, for example Glasrud et al 1993) and has been observed with both Hanford wastes and waste simulants (Rector and Bunker 1995). supernatant liquid or an equimolar sodium hydroxide and salt solution), differences in waste chemistry make applying these results to the current mobilization and retrieval scenario rather difficult.…”
Section: Settled Slurry Volume Fraction and Sedimentation Behaviorsupporting
confidence: 88%
“…6 indicates that the simulated dissipation of excess pore pressure is much slower than the dissipation observed in the experiment. We conjecture that this is due to the formation of vertical channels such as those photographed by Glasrud et al [36], through which the liquid flows upwards at an increased rate compared with its flow through the interstices of the sediment layer. The rapid dissipation of excess pore pressure could also be due to the plastic deformation of the sediment bed at high loads, i.e.…”
Section: Discussionmentioning
confidence: 92%
“…2 we show the sedimentation coefficient worked out from [12] after p m (r) was displaced by p(r). A typical value of the Hamaker constant for colloidal particles was chosen, viz.…”
Section: Sedimentation Of Magnetic Particles Affected By Van Der Waalmentioning
confidence: 99%
“…Peterson and Krueger studied the settling velocity of magnetic particles as a function of an applied magnetic field (11). Glasrud et al studied the settling behavior of strongly flocculated magnetic iron oxide particles qualitatively (12). Equations describing the concentration dependence of the sedimentation coefficient without an applied external magnetic field and when the applied magnetic field was infinitely strong were found by Dhont (10).…”
Section: Introductionmentioning
confidence: 98%